Celebrity endorsers role on brand equity: a qualitative study on Cristiano Ronaldo and Nike. - Lamberti, Bradley (The IIE, 2020)
The fight for market share in saturated industries has put immense pressure on marketing campaigns and how they can be made as effective as possible. The use of celebrity endorsers has become an increasingly popular marketing method for brands to increase their brand equity (Ahmed & Ashfaq, 2013). However, how does a business choose the right celebrity influencer for their brand and how important is this alignment? This research study aims at gaining an understanding of consumers perceptions of celebrity endorsers and the brand equity of the endorsing brand, with specific reference to Cristiano Ronaldo’s endorsement of Nike. Data was collected from participants who partook in an in-depth online interview involving open-ended questions that were constructed in relation to David Aaker’s model of brand equity. The most significant findings of this research study is that consumers need to be able to associate themselves with the celebrity endorser in order for them to be effective. The research also found an agreement with celebrity endorsers and their contribution towards the awareness of their endorsing brand.
Keywords: Marketing; Marketing campaign; Brand endorsement